Reference Intervals for Conventional Transthoracic Echocardiography and Two-Dimensional Speckle Tracking Echocardiography-Derived Strain Values in the Dutch Sheepdog (‘Schapendoes’) - Dinand Favier; Celine Brugada-Terradellas; Johannes Vernooij; Alma Hulsman; Giorgia Santarelli (Animals)
Echocardiographic values can vary between dog breeds, making breed-specific reference intervals (RIs) preferable. Two-dimensional speckle tracking echocardiography (2-D STE) is an advanced imaging technique that enables the measurement of myocardial deformation parameters, contributing to the assessment of systolic function. The objective was to determine breed-specific RIs for 2-D, M-mode, and Doppler-derived echocardiographic parameters for Dutch Sheepdogs, and to obtain 2-D STE-derived strain and strain rate values in this breed. Apparently healthy, purebred Dutch Sheepdogs (1–7 years) were recruited. Each dog underwent a physical examination and transthoracic echocardiography. Conventional 2-D, M-mode, and Doppler measurements were obtained; strain analysis was performed with 2-D STE software. RIs were established for conventional echocardiographic parameters; clinically relevant parameters were compared with commonly used RIs. The effects of gender, age, body weight (BW) and heart rate were tested. Sixty dogs were included. Panting and/or tachycardia were observed in 24 dogs, which affected the quality of the analysis to varying degrees (e.g., out-of-sector movement, lung artefacts). The selected parameters for left ventricular (LV) and atrial dimension showed good agreement with published RIs. BW was an independent variable influencing LV dimensions. This study provides RIs for conventional echocardiographic measurements and reports 2-D STE-derived strain and strain rate values obtained in Dutch Sheepdogs. The selected parameters of LV and left atrial dimension showed good agreement with commonly used RIs. Anxious behavior could represent a breed peculiarity to take into account when performing echocardiography, as it can affect image quality.